Studies towards the synthesis of 4-hydroxybenzyl 3-acyltetramic acid / Norhanim Mohalid - Mohalid, Norhanim (2016)
The tetramic acid (pyrrolidine-2,4-dione) ring system is present as a key structural unit in many natural products. In this project, a derivative of fuligorubin, namely 4- hydroxybenzylated 3-acyl tetramic acid from slime mold Leocarpus fragilis was chosen as the synthetic target not only due to its biological properties, but mainly due to the challenging structure of the hydroxybenzylated tetramic acid moiety. We were also synthesized fused ring (bicyclic) compounds and tetramic acid as the key structural unit. Our synthetic approach towards 4-hydroxybenzylated 3-acyltetramic acid started with the formation of key important tetramic acid ring system using two possible routes. The first route began with the benzylation of hydroxyl group of commercially available L-tyrosine, followed by 7V-Boc protection and a one-pot condensation and Dieckmann cyclisation. In this route, we managed to synthesize the required tetramic acid 3, in three steps with an overall yield of 37%. The second route began with the esterification of Z,-tyrosine, followed by condensation, Dieckmann cyclisation and demethoxycarbonylation to furnish the required tetramic ring 7, in four steps with 36% overall yield. The synthesized tetramic acid 3 was then subjected to acylation reaction using different acyl chlorides and reaction conditions to give the acylated tetramic acids 117 and 118 in 8-14% overall yields. Apart from these acylated products highlighted, several pyrrolidinone type compounds have been successfully synthesized towards the formation of fused ring (bicyclic) compounds. Our accomplishment in performing these reactions confirmed the feasibility of our synthetic strategy towards exploring new drugs based on pyrrolidinone moiety. This study may as well be used to develop new scientific knowledge and remarkable findings.